Molecular detection of Chlamydiales organisms in ruminant abortions in Brazil - Pinto, Ana Paula Vieira [UNESP]; Teixeira, Wanderson Sirley Reis [UNESP]; Malossi, Camila Dantas [UNESP]; Possebon, Fábio Sossai [UNESP]; Henker, Luan Cleber; Lorenzett, Marina Paula; Pavarini, Saulo Petinatti; Driemeier, David; Casagrande, Renata Assis; Araújo Júnior, João Pessoa [UNESP]; Megid, Jane [UNESP]; de Mioni, Mateus Souza Ribeiro [UNESP] (My University, 2025)
Infections caused by the Chlamydiales order are highly prevalent worldwide and have a well-known association with reproductive and non-reproductive disorders in livestock and humans. This study aimed to identify Chlamydiales organisms in ruminant abortions using real-time polymerase chain reaction (qPCR) in samples collected from three Brazilian states: Rio Grande do Sul, Santa Catarina, and São Paulo. The Chlamydiales order was found in 7.8% (18/231) of the samples, including 10 bovine and 8 ovine samples. For the Chlamydiaceae family, the positivity was 2.2% (5/231), with detection in one bovine and two ovine fetuses from Rio Grande do Sul, one ovine fetus from Santa Catarina, and one bovine from São Paulo. Chlamydiales positive samples detection with Ct value lower than 35 were subjected to Sanger sequencing and phylogenetic analysis, which revealed the presence of an organism belonging to the Waddliaceae family in a bovine fetus and two Simkaneceae bacteria in ovine fetuses. This study is the first report of Chlamydia-like organisms in ruminant abortions in Brazil, highlighting the importance of conducting further surveys to evaluate their role as abortifacient pathogens in the country.
Keywords: Cattle; Chlamydia; Fetus; Sheep; Simkaneaceae; Waddliaceae